State Institution and Socio Analysis on Sexual Violence in Higher Education - Achmad Achmad; Zakki Adlhiyati (Universitas Negeri Semarang, 2026)
The legal framework on sexual violence is getting stronger, but sexual violence still occurs in universities. The objectives of this research are, to analyze the legal framework for protection against sexual violence, to identify the challenges in solving the issue of sexual violence, to formulate a collaborative institutional model in addressing sexual violence. This research is a socio-legal research, examining the problem of sexual violence through an interdisciplinary framework, integrating juridical, sociological, and institutional perspectives. This study reveals three points: First, the legal framework for addressing sexual violence has been more progressive but there are several weaknesses, ie, (1) internal task force members from within the university, (2) lack cooporation from university and law enforcer in takin care of the issue, (3) no external supervisor from state institutions in the process of investigation. Second, based on Donald Black's theory, there are four variables influencing the issue of sexual violence, ie: power inequality that protects high-status perpetrators (stratification); preference for informal settlement rather than criminal justice proceedings (morphology); patriarchal culture; and institutional self-protection that prioritizes reputation over accountability (organization). Third, collaboration with state institutions Komnas Perempuan, LPSK, the Press Council, and the Ombudsman is needed as a balancing force for certain variables in the Black model. This integrated approach offers a path to rebalancing power relations, ensuring institutional accountability, and realigning law enforcement with principles of justice.